Angel Catbird. Volume 3, The Catbird roars - Atwood, Margaret, 1939- (Dark Horse Books, 2017)
It's all-out war in the madcap culmination of Angel Catbird's superhero saga. The evil Rat army is aiming for world domination, and only a ragtag gang of half-cats stands in their way.